Bosses matter: The effects of managers on workers' performance - Kathryn L. Shaw (IZA World of Labor, 2019)
A good boss can have a substantial positive effect on the productivity of a typical worker. While much has been written about the peer effects of working with good peers, the effects of working with good bosses appear much more substantial. A good boss can enhance the performance of their employees and can lower the quit rate. This may also be relevant in situations where it is challenging to employ incentive pay structures, such as when quality is difficult to observe. As such, firms should invest sufficiently in the hiring of good bosses with skills that are appropriate to their role.
Keywords: J24; 330; managers; bosses; peers; productivity